The Literature Review of Complementary Therapies for the Management of Gestational Diabetes Mellitus - afifa, irma; Gita Verlina Maya (International Journal Of Health Science, 2025)
Gestational diabetes mellitus is a condition of hyperglycemia in pregnant women caused by insulin resistance influenced by hormones produced by the placenta, such as placental lactogen. This can have adverse effects on the condition of pregnant women, leading to preeclampsia, as well as causing macrosomia and hypoglycemia in the fetus. The prevalence of gestational diabetes mellitus has increased by 10% among pregnant women, particularly in East Asia and Southeast Asia, where it stands at 10.1% and is more commonly found in low- and middle-income populations compared to high-income populations. Previous studies have examined the management of gestational diabetes through early screening and insulin therapy to normalize blood sugar levels in the body. This article discusses the management of gestational diabetes mellitus using complementary therapy to provide a better prognosis for the well-being of the mother and fetus without replacing the primary treatment prescribed by the doctor. This article used a literature review method to conceptualize and identify literature gaps in complementary therapy for managing gestational diabetes mellitus. Based on the results of the literature review, complementary therapy administered to pregnant women with diabetes mellitus can suppress the release of cortisol, a hormone with anti-insulin, leading to hyperglycemia in pregnant women. Further research is needed to develop a holistic approach in the care of pregnant women with GDM to prevent complications for both the mother and the fetus.